Traditional medicinal plant knowledge under anthropogenic pressure: evidence from the Middle Syrdarya botanical-geographical district, Uzbekistan - Kosimov, Zokir; Bussmann, Rainer W.; Beshko, N.Yu.; Naraliyeva, N.M.; Khujanazarov, U.E.; Mirzoyeva, M.A.; Kuzieva, S.U. (Ethnobotany Research and Applications, 2026)
Background: Strong anthropogenic transformation in semi-arid regions substantially alters native vegetation and threatens traditional medicinal plant knowledge. The Middle Syrdarya botanical-geographical district represents one of the most intensively modified landscapes in Central Asia, where natural ecosystems have largely been replaced by agroecosystems. Integrated assessments are therefore required to evaluate medicinal plant diversity, adventive components, and the persistence of ethnobotanical knowledge under such conditions. Methods: Field surveys were conducted between 2021 and 2025 across major landscape types of the Middle Syrdarya region. Medicinal plant species were recorded using floristic inventories, herbarium collections, and semi-structured interviews with local informants. Taxonomic composition, functional use categories, and adventive status were analyzed. The proportion of adventive species was applied as an indicator of floristic transformation, and functional traits were evaluated to assess ecosystem-related services of medicinal plants. Results: A total of 245 medicinal plant species belonging to 158 genera and 47 families were documented. Asteraceae (49 species), Fabaceae (19), and Lamiaceae (17) were the most species-rich families. Fifty-six species (22.9%) were identified as adventive, indicating pronounced anthropogenic influence on regional flora. Adventive representation was highest in Solanaceae (71.4%) and Malvaceae (54.5%), while no adventive medicinal species were recorded in Polygonaceae. Functional analysis revealed dominance of weed and melliferous species, suggesting that medicinal resources are increasingly derived from secondary and agroecosystems. Traditional knowledge was found to be reorganized around ecologically plastic and widespread species, whereas narrowly adapted aboriginal taxa are gradually disappearing from local practice. Conclusions: The high proportion of adventive medicinal plants reflects reduced ecosystem stability and ongoing floristic restructuring in the Middle Syrdarya region. Medicinal plants and associated traditional knowledge act as sensitive bioindicators of anthropogenic transformation. These findings provide a scientific basis for monitoring, conservation prioritization, and sustainable management of medicinal plant resources in transformed semi-arid landscapes. Keywords: Ethnobotany; medicinal plants; anthropogenic transformation; adventive species; traditional knowledge; ecosystem resilience; land-use change; Middle Syrdarya region; Uzbekistan